Development of The Digital Game Ce-Ria Based on Android for The Mathematics Subject of Class I Primary School Students - Lumbantobing, Winda Lidia (Sebatik, 2025)
This research will focus on developing Android-based digital games to support learning in mathematics subjects, especially for students in elementary schools. The aim of the research prepared is to find out the results of developing Android-based digital games in mathematics subjects for elementary school students. This research is recommended as a type of development research, namely the development of Android-based digital games in mathematics subjects for elementary school students. The game developed is a collection of digital materials via the Android platform which will become a learning medium for students. In this research, the development stage only reaches product validation. The results of the product feasibility test assessment, namely in the form of a game, show that the score obtained is in the range of 2.60 - 3.59. The development of Android-based games was successfully carried out with the theme of making learning more fun without making students burdened. The making of this game involved several parties consisting of elementary school teachers, lecturers, and practitioners in the fields of education and information technology. The game development material was created based on field needs, namely the difficulty of recognizing numbers and simple addition arithmetic operations. This game is intended for grade 1 elementary school students considering that the characteristics of students at that age are in the playing phase, so the development of a game with educational elements is suitable and appropriate for grade 1 students, and can make it easier for teachers to convey the material.